ANALISIS ALTMAN Z-SCORE, GROVER SCORE, SPRINGATE, DAN ZMIJEWSKI SEBAGAI SIGNALING FINANCIAL DISTRESS (Studi Empiris Industri Barang-Barang Konsumsi di Indonesia) - Primasari, Niken Savitri (UNUSA Press, 2017)
This study purpose to determine whether there are differences among Altman model, Springate model and Zmijewski model to predict financial distress, and to find out which the Financial Distress prediction model has the most excellent implementation in Indonesia manufacture industry. Comparison of those six models were made by analyzing the accuracy of each model, by using the real condition of a company’s net income. The data used in the form of annual financial statements published by the company on the Indonesia Stock Exchange website. The sample in this study consisted of 116 financial data from 29 companies in Consumer Goods Industry. All companies are listed in Indonesia Stock Exchange Market at period 2012 - 2015. The company does not conclude yet, whether there is a prediction model that best suit the measurement. This cause by: (1) every model have its own superiority and weakness, (2) the company sample characteristic differences (company sector, company size) also influence the choice of prediction model being used, (3) the company financial ratio as independent variable used in bankruptcy prediction. Since the financial statements are reflecting the company’s financial ability of the signaling, the researchers limited the industry with the highest value of EPS and PER. This is done to avoid confounders in the proof of the accuracy of the model, Springate model, Ohlson model and Zmijewski model to predict financial distress. The data obtained from the Annual Financial Statements, IDX Fact Book and the Indonesian Capital Market Directory. In this study will be used t test, additional testing is done to see the feasibility of the model by observing the F test results and test the coefficient of determination (R2), R2 value used to examine differences among Altman, Grover, Springate and Zmijewski models in predicting financial distress. The analytical tool used is the One Way ANOVA with level of significance 5 %. The results from this research showed that any prediction model used in this study can be used to predict Financial Distress, particularly the Altman Z-Scores, which have the greater R2 analysis. Only Grover G-Score models have insignificant value t test and F-test is greater than the probability cannot be used to predict corporate Financial Distress. The results also showed that the most accurate model is the model Altman Z-Score. At the end of the study was to try predict 29 firms sample used listed on the Stock Exchange with Altman model. Predicted results showed that five companies are expected to experience Financial Distress in the future.